On the Fungibility of Spending and Earnings : Evidence from Rural China and Tanzania - Christiaensen, Luc (World Bank, Washington, DC, 2013)
A common behavioral assumption of micro-economic theory is that income is fungible. Using household panel data from rural China and Tanzania, this study finds however that people are more likely to spend unearned income on less basic consumption goods such as alcohol and tobacco, non-staple food, transportation and communication, and clothing, while they are somewhat more likely to spend earned income on basic consumption goods such as staple food, and invest it in education. This resonates with the widespread cultural notion that money that is easily earned is also more easily spent. Cognitively, the results could be understood within the context of emotional accounting, whereby people classify income based on the emotions it evokes, prompting them to spend hard earned money more wisely to mitigate the negative connotations associated with its acquisition. The policy implications are real, bearing for example on the choice between employment guarantee schemes and cash transfers in designing social security programs.